Type V hypertriglyceridemia in children, a therapeutic challenge in pediatrics: A case report and a review of the literature. Issue 51 (December 2017) - Mărginean, Cristina Oana; Meliţ, Lorena Elena; Dobreanu, Minodora; Mărginean, Maria Oana
Abstract: Rationale: Hypertriglyceridemia is defined as a level of triglycerides above 150 mg/dL. The complex causes and classification of hypertriglyceridemia lead to difficulties in the diagnosis and management of this condition. Patient concerns: We present the case of a 15 years and 6 months old female teenager, admitted in our clinic for the following complaints: severe abdominal pain predominantly in the lateral left quadrant, nausea, vomiting, and the lack of stools for 2 days. The clinical exam showed: impaired general status, painful abdomen at superficial and deep palpation in the left and upper abdominal quadrants, the absence of stools for 2 days. Diagnoses: The laboratory parameters revealed leukocytosis with neutrophilia, thrombocytopenia, high level of serum amylase and triglycerides, and increased inflammatory biomarkers. The imagistic investigations showed ascites and paralytic ileus. Interventions: The management was burdened by the side-effects of hypolipidemic drugs impairing the liver function and leading to rhabdomyolysis, but eventually the patient's outcome was good. Outcomes: Type V hyperlipoproteinemia is a rare condition accounting for approximately 5% of the cases. The risk for acute pancreatitis is well-known to be associated with hypertriglyceridemia, even though in rare cases. Lessons: The prognosis of hypertriglyceridemia is pediatrics is burdened not only by the long-term risk factors associated to the diseases itself, but also by the negative effects of long-term hypolipidemic treatment.